1989
DOI: 10.2307/2061490
|View full text |Cite
|
Sign up to set email alerts
|

Relative deprivation and international migration oded stark

Abstract: This article provides theoretical reasoning and empirical evidence that international migration decisions are influenced by relative as well as absolute income considerations. Potential gains in absolute income through migration are likely to play an important role in households' migration decisions, but international migration by household members who hold promise for success as labor migrants can also be an effective strategy to improve a household's income position relative to others in the household's refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
234
0
57

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 400 publications
(300 citation statements)
references
References 14 publications
9
234
0
57
Order By: Relevance
“…Studies on remittances and socio-economic development like Gupta, (2009), Siddiqui andKemal (2006), Insights (2006) and Adams and Page (2005) argued that remittances has both a welfare effect (via directly alleviating poverty of the recipient family) since the 'really deprived' households are more likely to engage in international migration, and they end up with relatively 'better-off' position with remittances (Stark and Taylor, 1989;Adam 1993). Adam and Page (2005) in a comprehensive study using 71 developing countries data concluded that both international migration and remittances significantly reduce the level, depth, and severity of poverty in the developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on remittances and socio-economic development like Gupta, (2009), Siddiqui andKemal (2006), Insights (2006) and Adams and Page (2005) argued that remittances has both a welfare effect (via directly alleviating poverty of the recipient family) since the 'really deprived' households are more likely to engage in international migration, and they end up with relatively 'better-off' position with remittances (Stark and Taylor, 1989;Adam 1993). Adam and Page (2005) in a comprehensive study using 71 developing countries data concluded that both international migration and remittances significantly reduce the level, depth, and severity of poverty in the developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Measures of relative deprivation were proposed by Becker (1974), Yitzhaki (1979), and others. For evidence on the significance of relative deprivation in human affairs see, for example, Stark and Taylor (1989), Walker and Smith (2002), Eibner and Evans (2005), Luttmer (2005), and Clark et al (2008).…”
Section: Modeling the Assimilation Behavior Of Migrantsmentioning
confidence: 99%
“…) One branch of this body of research has dealt with migration. Several studies have shown empirically that a concern for relative deprivation impacts significantly on migration outcomes (Stark and Taylor 1989;Stark and Taylor 1991;Quinn 2006;Stark et al 2009). Theoretical expositions have shown how the very decision to resort to migration and the choice of migration destination (Stark 1984;Stark and Yitzhaki 1988;Stark and Wang 2007;Stark and Fan 2011;Fan and Stark 2011), as well as the assimilation behavior of migrants (Fan and Stark 2007), are modified by a distaste for relative deprivation.…”
Section: Why a Merger Of Populations Without Marriages Increases Unhamentioning
confidence: 99%